ASSESSMENT OF POTENTIAL DRUG INTERACTIONS AMONG HOSPITALIZED PATIENTS IN NEUROLOGY DEPARTMENT IN TERTIARY CARE HOSPITALS - DAIS, DIJO; CHERUVATHOOR, RANJEET AVIS; R, KAMESWARAN; RAJAGOPAL, SHANMUGA SUNDARAM (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: This research was instigated to determine and assess the prevalence, severity, type, and the total number of potential drug interactions in the neurology department of two hospitals in India. Methods: The data were collected from the prescriptions and by patient history interview on a daily basis. The drug-drug interactions (DDIs) were identified using Micromedex® database-2.7 and drugs.com. Results: The drug interactions were influenced by a plethora of risk factors: Gender, age, comorbidities, length of hospital stay, and the neurological condition. The study was comprised 320 patients, among 196 patients were identified with potential DDIs (PDDIs), and a total of 450 PDDIs were observed. The prevalence of PDDIs according to the severity was major (42.6%), moderate (45.11%), and minor (12.22%). Conclusion: To lessen PDDIs, the range of medications for the patients must be properly managed, and it is encouraged to remove all medicines without therapeutic advantage, intention, and an indication.